Radar observations of thunderstorms at Poona - MANI, A.; VENKITESHWARAN, S. P. (MAUSAM, 1961)
Radar observations of rain have ’been made at Poona since 1953, when a small air-borne model search radar type SCR-717-C operating on 9.1 cm was set up at the Poona Observatory. The radar has a peak power of 40 KW and a pulse length of 1.125 p, s. The antenna is a dipole-fed paraboloid mounted for rotation about a horizontal axis so that the radar beam scans the sky from horizon to horizon through the zenith giving a vertical cross-section through the atmosphere above the point of observation.